Composite materials in compression - Wind, Jens Lycke (Technical Report Mechanical Engineering, 2013)
A geometric and material non-linear finite element code is built using Matlab. The theoretical derivations for building the code is outlined and explained by pseudo code. Three different solvers are introduced; the Newton Raphson method, the modified Newton Raphson method, and the arc length method. The code is tested for material non-linearity an geometric non-linearity separately using standard reference solutions. The future work is outlined as a continuity of this report.